The information content of alternative monetary aggregates simple-sum versus divisia money in selected Asian countries - Habibullah, Muzafar Shah (The Philippine Review of Business and Economics, 1998)
The use of Divisia monetary aggregate has been proposed in the economic literature to take into account the different degrees of liquidity of the interest-bearing ﬁnancial assets included in defining ?money?. Despite the theoretical implication of the Divisia approach as an appropriate measurement of monetary services, the investigation has been mostly limited to developed countries. In this paper, the approach is applied to Asian monetary aggregates; the performance of the Divisia monetary aggregates together with its counterpart, the conventional Simple-sum aggregates, were then tested for their information content about national income using Granger-causality technique. Our results suggest that there is a role for Divisia monetary aggregate as intermediate indicator for policy purposes in the ?deregulated? Asian economies.